Epidemiology of primary biliary cholangitis in Italy: Evidence from a real-world database. Issue 5 (May 2019) - Marzioni, Marco; Bassanelli, Chiara; Ripellino, Claudio; Urbinati, Duccio; Alvaro, Domenico
Abstract: Background: Primary biliary cholangitis is an autoimmune disease affecting the interlobular bile ducts. Limited information is available on its epidemiology and treatment in Italy. Aims: To describe primary biliary cholangitis epidemiology and investigate treatment patterns for Italian patients with this disease. Methods: Electronic medical records from 900 general practitioners (part of the QuintilesIMS™ Longitudinal Patient Databases) were examined. Demographics were compared with those from the Italian National Institute of Statistics dataset. The International Classification of Diseases, Ninth Revision, biliary cirrhosis code 571.6 was used for diagnosis, and data on comorbidities, concomitant medications, medical examinations, specialist referrals, and treatments were collected. Results: This dataset was representative of the Italian population. Point prevalence of primary biliary cholangitis was calculated as 27.90 per 100, 000 and incidence as 5.31 per 100, 000 inhabitants/year. Some associations between the disease and comorbidities were sex specific. The most common laboratory assays requested were for liver enzymes, and the majority of patients were not referred to a specialist. Ursodeoxycholic acid was the most common therapy. Conclusion: This can be used as a benchmark for monitoring and identifying unmet needs to improve treatment in Italy.